Examining Predictors of Depression Among Older Incarcerated Women - Aday, Ron H. (Women & criminal justice, 2019)
For older women in prison, adjustments to prison life are often affected by a variety of mental and physical health symptoms. Many come to prison with specific histories of traumatic life experiences that place them at risk for high levels of depression. Using data gathered from 327 older women (mean age = 56.5), we examined the relationship between a variety of preprison conditions and prison deprivation factors as possible predictors of depression. Stepwise regression results indicated that depression was greater for those with prior abuse histories, functional health problems along with poorer perceptions of mental and physical health, safety and other prison environment concerns. Although race was not a significant predictor in the regression model, a t-test did find that whites were more depressed than African Americans in our sample. Other correlates of depression are also identified that lend insights into the high rates of depression found among elderly women in prison. With such high rates of psychiatric disorders among women offenders, more treatment interventions are needed to adequately serve this population.